Pleural abnormalities predating the development of mesothelioma - Hassan, M; Asciak, R; Hallifax, R; Mercer, R; Rahman, N (BMJ Publishing Group, 2017)
Mesothelioma is an aggressive tumour of the pleura that is closely related to asbestos exposure. Asbestos is known to cause benign pleural thickening, effusion and plaques and the majority of patients with these abnormalities do not develop mesothelioma. It has been noted, however, that asbestos-exposed patients who have pleural plaques are at increased risk of mesothelioma. This study aimed to describe the range of pleural abnormalities seen on CT done at some time before the diagnosis of mesothelioma was made.